Antimicrobial susceptibility and phylogenetic analysis of Propionibacterium acnes isolated from acne patients in Japan between 2013 and 2015. Issue 11 (17th June 2017) - Nakase, Keisuke; Hayashi, Nobukazu; Akiyama, Yui; Aoki, Sae; Noguchi, Norihisa
Abstract: The prevalence of antimicrobial‐resistant Propionibacterium acnes strains isolated from acne patients has been increasing in Japan. Here, to estimate the current resistance rate, we tested antimicrobial susceptibility among P. acnes from acne patients having visited a specialized dermatology clinic between 2013 and 2015. Rates of resistance to macrolides and clindamycin were 44.3 (31/70) and 38.6% (27/70), respectively. erm (X), which confers high‐level clindamycin resistance (minimum inhibitory concentration ≥256 μg/mL), was detected in six isolates, whereas no resistance determinants were identified in eight strains showing high‐level resistance to clindamycin. Using single‐locus sequence typing, the P. acnes isolates were classified into five clades (A, E, F, H and K), with all high‐level clindamycin‐resistant strains lacking known clindamycin resistance determinants being grouped together (in clade F). P. acnes isolates from patients previously treated with macrolides and clindamycin showed a macrolide resistance rate (55.3%) significantly higher than that of those from patients not having received these treatments (21.7%, P < 0.05). Furthermore, strains of clade F, which were very rarely isolated from healthy individuals, were more frequently recovered from patients with severe acne (40.0%) than those with mild acne (23.3%). Our data showed an increase in macrolide‐resistant P. acnes prevalence in Japan due to the use of antimicrobial agents for acne treatment. Furthermore, we identified strains of specific phylogenetic groups frequently associated with severe acne patients.